2002
DOI: 10.1590/s0066-782x2002001100001
|View full text |Cite
|
Sign up to set email alerts
|

Study of Coronary Sinus Flow Reserve Through Transesophageal Doppler Echocardiography in Normal Subjects

Abstract: Objective -To evaluate the Coronary Flow Reserve in the Coronary Sinus through transesophageal Doppler echocardiography in normal subjects. Methods - Study of Coronary Sinus Flow Reserve Through Transesophageal Doppler Echocardiography in Normal SubjectsOriginal ArticleThe capacity to increase coronary blood flow in response to an appropriate stimulus was determined by coronary flow reserve (CFR) or vasodilatating coronary reserve CSF by TEE can be monitored within a distance of 1 to 1.5 cm, from the ostium wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Over the last decade, coronary flow reserve (CFR) in the CS has been used to diagnose significant coronary artery stenosis by transesophageal Doppler echocardiography (TEE) due to an inadequate visualization of the coronary arteries, especially their mid- and distal parts (57). TEE is a semi-invasive procedure and vasodilator drugs, such as adenosine, are not always harmless.…”
mentioning
confidence: 99%
“…Over the last decade, coronary flow reserve (CFR) in the CS has been used to diagnose significant coronary artery stenosis by transesophageal Doppler echocardiography (TEE) due to an inadequate visualization of the coronary arteries, especially their mid- and distal parts (57). TEE is a semi-invasive procedure and vasodilator drugs, such as adenosine, are not always harmless.…”
mentioning
confidence: 99%
“…They are all in vivo studies using transesophageal and transthoracic Doppler echocardiography [10][11][12][13][14]17,18], and none of these studies provided the precise correlation between the coronary sinus flow and the coronary infusion. Compared with in vivo studies, our study had some possible advantages.…”
Section: Discussionmentioning
confidence: 99%
“…Although a large number of clinical and experimental studies have validated the efficiency of retrograde coronary sinus perfusion [3][4][5][6][7][8][9], the studies on the diagnostic performance of coronary sinus flow detected by Doppler echocardiography in coronary artery disease are not yet rich enough. Over the last decade, the coronary flow reserve in the coronary sinus has been used to diagnose severe coronary artery stenosis by transesophageal Doppler echocardiography due to inadequate visualization of the coronary arteries [10][11][12]. Recently, our studies showed that coronary sinus flow depicted by transthoracic Doppler echocardiography at rest can detect coronary artery stenosis in non-hypertensive [13], hypertensive [14], and diabetic hypertensive patients.…”
Section: Introductionmentioning
confidence: 99%
“…The average value of three spectral and planimetric envelopes was used. Global left ventricular perfusion (mL/minute g) = the flow per minute/LVM (M-mode) (3). …”
Section: Methodsmentioning
confidence: 99%
“…The assessment of the coronary artery stenosis by conventional echocardiography remains challenging due to inadequate visualization of the coronary arteries, especially for the mid and distal parts (1-3). As 95% of the left ventricular perfusion drains to the right atrium through the coronary sinus (4), the flow in this vessel is a good representation of the global left ventricular perfusion.…”
Section: Introductionmentioning
confidence: 99%